Film copyright in the European Union - Kamina, Pascal (Cambridge University Press, 2002)
In the first book on this subject, Kamina analyses film protection in the fifteen member states of the EU, with emphasis on Britain and France. He addresses key aspects of film copyright, including the protection of film works within the EU in the context of European harmonization of copyright laws.
Keywords: Copyright -- Motion pictures -- European Union countries.; Copyright -- Motion pictures -- Great Britain.; Copyright -- Motion pictures -- France.; Droit d'auteur -- Cinéma -- Pays de l'Union européenne.; Droit d'auteur -- Cinéma -- Grande-Bretagne.; Droit d'auteur -- Cinéma -- France.; LAW -- Administrative Law & Regulatory Practice.; Copyright -- Motion pictures; European Union countries; France; Great Britain; Auteursrecht.; Films.; Europees recht.; Electronic books.